2017
DOI: 10.1016/j.colsurfb.2017.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Light-triggered release from dye-loaded fluorescent lipid nanocarriers in vitro and in vivo

Abstract: Light is an attractive trigger for release of active molecules from nanocarriers in biological systems. Here, we describe a phenomenon of light-induced release of a fluorescent dye from lipid nano-droplets under visible light conditions. Using auto-emulsification process we prepared nanoemulsion droplets of 32nm size encapsulating the hydrophobic analogue of Nile Red, NR668. While these nano-droplets cannot spontaneously enter the cells on the time scale of hours, after illumination for 30s under the microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 67 publications
(76 reference statements)
1
24
0
Order By: Relevance
“…The leakage of dyes was evaluated by fluorescence correlation spectroscopy (FCS) ( Table 1). [64][65][66] FCS is a powerful tool to characterize NPs size 67 and polydipersity, 68 as well as to evaluate their behavior in biological media, 69 including their stability, 70,71 and formation of protein corona on the surface of NPs. 72,73 Recent studies showed the possibility to use FCS to study leakage of dyes from unilamellar lipid vesicles, 74 and lipid nano-droplets directly in biological media.…”
Section: Scheme 1 (A)mentioning
confidence: 99%
“…The leakage of dyes was evaluated by fluorescence correlation spectroscopy (FCS) ( Table 1). [64][65][66] FCS is a powerful tool to characterize NPs size 67 and polydipersity, 68 as well as to evaluate their behavior in biological media, 69 including their stability, 70,71 and formation of protein corona on the surface of NPs. 72,73 Recent studies showed the possibility to use FCS to study leakage of dyes from unilamellar lipid vesicles, 74 and lipid nano-droplets directly in biological media.…”
Section: Scheme 1 (A)mentioning
confidence: 99%
“…Although DBS dyes were shown to have reduced brightness in non-viscous environments, in bioimaging experiments such dye leakage phenomenon can lead to decreasing of NEs brightness itself and thus enhancing the background noise. 21,59 In order to estimate the dye leakage, Fluorescent Correlation Spectroscopy (FCS) measurements were conducted in PBS alone and in the presence of 10 %(v/v) fetal bovine serum (FBS) ( Table 3). Serum is an appropriate model of biological dye acceptor as it contains a high variety of amphiphilic biomolecules especially lipoproteins.…”
Section: Dbs Loaded Fluorescent Nementioning
confidence: 99%
“… 30 , 31 FCS serves as a tool for measuring the size 32 and polydispersity 33 of nanoparticles, as well as for evaluating their behavior in complex biological media 34 and their stability. 35 , 36 Also in many reports, FCS has been used to characterize the formation of the protein corona on the surface of nanoparticles 37 − 39 or the interaction of human serum albumin with liposomes. 40 However, only few studies have reported the use of FCS to study the release of cargo from nanoparticles.…”
Section: Introductionmentioning
confidence: 99%